Tutoring using a mastery learning calculus computer courseware: is it effective? - Mohd Ayub, Ahmad Fauzi; Tengku Sembok, Tengku Mohd; Wong, Su Luan (Malaysian Educational Technology Association, 2007)
Teaching and learning approaches at the university level should be realigned to suit students’ ability level. It should also focus on the understanding of concepts, simplifying difficult concept and making students feel that calculus is an important subject not only during their studies but also in the future. The used of multimedia interactive courseware with its ability to visualize concepts will help lecturers to explain calculus concepts, which previously, cannot be illustrated through the conventional method of teaching. This paper will discuss the effectiveness of the Mastering Calculus Computer Courseware (MACCC) on the achievement of diploma students in the subject Calculus. Therefore, this paper will discuss the effectiveness of MACCC versus traditional tutorial type on the achievement of diploma students in the subject of mathematic Calculus. This research is a quasi-experimental research involving students from intact groups assigned to a control (28 students) and treatment groups (23 students). The analysis revealed that there was statistically significant difference between students’ achievement in the control and treatment groups where students from control group performed better than students from treatment group. This research implies that instructors could use MACCC only as a supplemental tool.